PENGEMBANGAN INSTRUMEN PENILAIAN RANAH AFEKTIF PADA MATA PELAJARAN BIOLOGI DI SMA - Amri Amri (Jurnal Biotek, 2016)
This study aimed to produce the valid and reliable assessment instrument for affective domain in measuring the affective skill of high school students in the subjects of biology. Type of this research is the research development by using an Instrument Development method with twice trial and errors, 68 people on the first trial and 120 people in the second trial. In the first test successfully extracted two factors, the reliability coefficient that is indicated by an alpha internal consistency which equals to 0.865. The second trial also successfully extracted two factors, the alpha internal reliability coefficient obtained for 0.892. It can be concluded that the assessment instrument for affective domain developed has good construct validity and very high internal reliability coefficient.